Social correlates of variation in urinary oxytocin concentrations of mantled howler monkeys Alouatta palliata (Gray, 1849) (Primates: Atelidae): A preliminary assessment - Moreno-Espinoza, Diana; Dias, Pedro Américo D.; Coyohua-Fuentes, Alejandro; Canales-Espinosa, Domingo; Rangel-Negrín, Ariadna (Instituto de Ecología, A.C., 2021)
There is growing evidence that non-human primate sociality is linked to proximate neuroendocrine mechanisms. Arginine vasopressin, endorphins, and oxytocin may be involved in such mechanisms. Here, we perform a preliminary analysis of the social correlates of variation in urinary oxytocin concentrations in mantled howler monkeys (Alouatta palliata). From January to December 2017, we studied 13 adult mantled howler monkeys belonging to two groups. We recorded the occurrence of social interactions (547.5 observation hours); assessed proximity among group members (2,194 instantaneous recordings); and collected 172 urine samples. Urine samples were assayed (ELISA) for oxytocin concentrations, which were corrected for specific gravity, resulting in 54 analyzed samples. Hormone concentrations increased by approximately 62% when individuals were involved in affiliative interactions. With respect to when no affiliative interactions occurred, urinary oxytocin concentrations were higher when dyads with a low-quality social relationship affiliated. These results agree with previous contentions that this hormone is linked to participation in affiliative interactions. Convergence between these and results from other taxa supports the hypothesis that the biological mechanisms that allow for primate sociality are shared among species.